“Lo stupore negli occhi dell’altro”. John Berger e l’immagine del desiderio - Brotto, Denis (Scenari, 2021)
For John Berger, visual culture is not a mere instance of the present. In line with Bredekamp, Mitchell, Freedberg, Berger emphasizes how visual culture settles in the past and has origins that connect with the story itself of the image, with its cultural and social significance. The understanding of an image is moreover connected to the perception of the desire that it produces. In his works, the relationship between image and desire concerns images of pictorial art, cinema, photography, but also virtual ones produced by literature, poetry, music. For Berger, the gaze is the correlation factor to understand what images produce in terms of knowledge, identification, attraction. Reflecting on vision becomes a way to observe our own desire, to investigate its hidden origins, and its ability to withstand possible erosion factors.